2023
DOI: 10.1093/braincomms/fcad164
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies from serum and CSF of multiple sclerosis patients bind to oligodendroglial and neuronal cell-lines

Abstract: Multiple sclerosis is a highly complex and heterogeneous disease. At onset it often presents as a clinically isolated syndrome. Thereafter relapses are followed by periods of remissions, but eventually most patients develop secondary progressive multiple sclerosis. It is widely accepted that autoantibodies are important to the pathogenesis of multiple sclerosis, but hitherto it has been difficult to identify the target of such autoantibodies. As an alternative strategy, cell-based methods of detecting autoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…34 Other authors demonstrated that antibodies from MS patients bind to oligodendroglial and neuronal cell-lines. 35 Recently, is was demonstrated that OgIgGBs target debris. 21 These data indicate that IgG also plays a pathogenic role.…”
Section: Introductionmentioning
confidence: 99%
“…34 Other authors demonstrated that antibodies from MS patients bind to oligodendroglial and neuronal cell-lines. 35 Recently, is was demonstrated that OgIgGBs target debris. 21 These data indicate that IgG also plays a pathogenic role.…”
Section: Introductionmentioning
confidence: 99%